The Effect of Garlic Decoction (Allium sativum L.) on The Histological Features of The Liver of Alloxan-induced Mice (Mus musculus) - Kodariah, Liah; Karimah, Haniefatul; Purwaeni, Purwaeni; Fadilah, Tyas Ismi (Lighthouse Publishing, 2023)
Giving alloxan can cause disruption of insulin production resulting in hyperglycemia. Hyperglycemia causes Reactive Oxygen Species (ROS) resulting in oxidative stress and liver cell damage. The use of natural ingredients, one of which is garlic (Allium sativum L) in the form of boiled water, because it contains flavonoid and organosulfur compounds. Therefore, the purpose of this study was to determine the histology of the liver of mice (Mus musculus) induced by alloxan after being given a decoction of garlic (Allium sativum L). This study used experimental research with a completely randomized design method on mice consisting of 6 groups with 4 replications each. The groups in this study consisted of a negative control group (without treatment), a positive control group (alloxan injection) a comparison control group (alloxan injection + glibenclamide) treatment groups at doses I, II and III (alloxan-induced + garlic boiled water (Allium sativum L) respectively 20 gr, 40 gr and 60 gr). Histology of the liver of mice (Mus musculus) was made by paraffin method with Hematoxylin Eosin (HE) staining. The result showed that there was a significant difference due to the value (p<0,05) but for a KP and P3 there was no significant difference with the value (p>0,05) on hydropic degeneration. Based on the results of the study, it can be concluded that the decoction of garlic (Allium sativum L) has an effect on the alloxan-induced liver histology of mice (Mus musculus).